Can endoscopic retrograde cholangiopancreatography‐related procedures for resolving acute cholangitis be effectively and safely performed in patients with surgically altered anatomy? Comparison study to evaluate the timing of short‐type single‐balloon enteroscopy‐assisted endoscopic retrograde cholangiopancreatography. Issue 3 (18th October 2022) - Tanisaka, Yuki; Mizuide, Masafumi; Fujita, Akashi; Jinushi, Ryuhei; Shiomi, Rie; Shin, Takahiro; Hirata, Dai; Terada, Rie; Tashima, Tomoaki; Mashimo, Yumi; Ryozawa, Shomei
Abstract : Objectives: Balloon enteroscopy (BE)‐assisted endoscopic retrograde cholangiopancreatography (ERCP)‐related procedures to resolve acute cholangitis (AC) in patients with surgically altered anatomy (SAA) are limited. There is a lack of evidence on whether the timing of BE‐assisted ERCP affects clinical outcomes in patients with AC. This study aimed to evaluate the clinical outcomes of short‐type single‐balloon enteroscopy (short SBE)‐assisted ERCP in patients with SAA and AC. Methods: Patients with AC who underwent short SBE‐assisted ERCP procedures between September 2011 and April 2022 were retrospectively reviewed. The outcomes of procedures undergone at ≤24 h and >24 h were compared. The primary outcome was the length of stay (LOS). Results: Overall, 56 patients underwent procedures at ≤24 h, and 58 patients at >24 h. The procedural success and adverse event rates of short SBE‐assisted ERCP were 87.7% (95% confidence interval [CI] 80.3–93.1%) and 4.4% (95% CI 1.4–9.9%), respectively. Patients with severe (Grade III) AC and systemic inflammatory response syndrome were more in early (at ≤24 h) ERCP groups. LOS and median time from ERCP procedures to discharge were shorter in the early group. Procedural success and adverse event rates between both groups had no significant differences. Multivariable linear regression analysis showed that ERCP performed at ≤24 h was associated with shorter LOS, while severe cholangitis and malignant biliary obstruction were associated with longer LOS. Conclusions: Short SBE‐assisted ERCP is effective and safe in patients with SAA and AC. Early procedures seemed to attribute early improvement of general condition, thus shortening the LOS.